2014
DOI: 10.1016/j.jped.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Study of the association between 3111T/C polymorphism of the CLOCK gene and the presence of overweight in schoolchildren

Abstract: The CLOCK 3111T/C polymorphism was not significantly associated with overweight or sleep duration in children in this city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
11
0
2
Order By: Relevance
“…With regard to the minor allele (G) of rs1801260, several studies of this SNP in the general adult population and school-age children identified a similar effect as did the current study, which suggest the minor allele of rs1801260 is linked to higher BMI [10,14,15,23,24]. The minor allele of rs1801260 was related to the expression level of the CLOCK gene and consequently might affect the CLOCK-related obesogenic mechanism.…”
Section: Plos Onesupporting
confidence: 80%
See 3 more Smart Citations
“…With regard to the minor allele (G) of rs1801260, several studies of this SNP in the general adult population and school-age children identified a similar effect as did the current study, which suggest the minor allele of rs1801260 is linked to higher BMI [10,14,15,23,24]. The minor allele of rs1801260 was related to the expression level of the CLOCK gene and consequently might affect the CLOCK-related obesogenic mechanism.…”
Section: Plos Onesupporting
confidence: 80%
“…Thus far, few studies have assessed the association of the CLOCK gene with obesity in the pediatric population. Giovaninni et al (n = 340) [ 23 ] and Valladares et al (n = 256) [ 24 ] both assessed the relationship of rs1801260 with BMI in school-age children. Although the association did not reach statistical significance, children who carried the minor allele had a higher rate of overweight and/or BMI z-scores in their studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 393 articles were read in full, with 281 excluded: 120 did not meet the age criteria (5‐13 years); 8 were of clinical or nonfree‐living population groups; 8 did not measure weight status objectively; 68 did not analyze the association between sleep‐obesity; and 77 were excluded either due to being non‐English, not peer‐reviewed, review/meta‐analysis, duplicate data, or a conference abstract/other unpublished data. This left 112 articles deemed relevant and included in the analysis (Table ) …”
Section: Resultsmentioning
confidence: 99%